Pyridine/Pyrimidine Substituted Imidazol-5-one Analogs as HIV-1 RT Inhibitors: Design, Synthesis, Docking and Molecular Dynamic Simulation Studies - Mokale, Santosh; Lokwani, Deepak; Mujaheed, Abdul (Current HIV Research, 2021)
Background: This paper reports the synthesis, Non-nucleoside reverse transcriptase inhibitory (NNRTIs) activity and computational studies of 2-((4-chloro-2-subtitutedphenoxy) methyl)-4-(furan-2-ylmethylene)-1-substituted Pyridine/-pyrimidine-1H-imidazol-5(4H)-ones. Methods: The imidazol-5-one analogs were synthesized by conventional method and characterized by FT-IR, NMR and mass spectral data. All compounds were evaluated for in-vitro NNRTI activity by using reverse transcriptase (RT) assay kit (Roche). The in-silico docking studies were conducted on RT enzyme to investigate binding site interactions of synthesized compounds. The MMGBSA method was also used to calculate the binding free energy between the inhibitors and RT enzyme. The MD simulation was further performed for the apo form of the RT enzyme and docked complex of compound A6-RT enzyme to better understand the stability of the protein-ligand complex. Results: The bioactivity analysis revealed that most of the synthesized compounds showed significant inhibitory activity against RT enzyme and the IC50 value was found to be in the range of 1.76-3.88 μM. The computational studies suggest that the docked compounds form the H-bonding with amino acid residue Lys101 and hydrophobic interactions with amino acid residues Tyr188, Tyr181, Trp229, and Tyr318, which act as the primary driving forces for protein-ligand interaction. Conclusion: The reported imidazol-5-one analogs can act as lead for further development of prospective RT inhibitors.
Keywords: MMGBA